Pengaruh Edukasi Terhadap Perilaku Penggunaan Obat Tradisional Di Desa Babai Kecamatan Karau Kuala Di Masa Pandemi Covid-19 - Gina Aulia Istiqomah; Rina Saputri; Sismeri Dona (LPPM Universitas Sari Mulia, 2021)
The Effect of Education on Behavioral Using Traditional Medicines in Babai Village, Karau Kuala District During the Covid 19 Pandemic. Supervised by RINA SAPUTRI and SISMERI DONA Background: Inappropriate drug use behavior greatly affects the success of therapy and the emergence of unwanted reactions from treatment. This inaccuracy of public behavior can occur because of the lack of public knowledge about drug information. Efforts to increase knowledge is to provide education. So an educational effort is needed, there are many educational media that can be used, one of which is video. Objective: This study aims to analyze how the influence of education on the behavior of using traditional medicine in Babai Village, Karau Kuala Sub-district during the Covid-19 pandemic. Method: True experimental research with pretest and posttest group design approach. Sampling was done by purposive sampling. The research sample amounted to 100 respondents. The data was obtained by using a questionnaire which was distributed using google form media. Results: Community behavior towards the use of traditional medicine in Babai Village, Karau Kuala sub-district, seen from the pretest results, only 50% of the people behaved positively out of 100 respondents who used traditional medicine. After providing education to the intervention group, there was an improvement in positive behavior of 62.0%. The results of the SPSS analysis with logistic regression test showed a p-value of 0.045 <0.05 which indicated that there was a significant effect on the provision of education. Conclusion: There is an effect of providing education with video media on the behavior of respondents towards the use of traditional medicine in Babai Village, Karau Kuala Sub-district during the covid19 pandemic. Keywords: Behavior, education, video